Nitrogen-controlled intra- and interspecific competition between Populus purdomii and Salix rehderiana drive primary succession in the Gongga Mountain glacier retreat area. (3rd March 2017) - Song, Mengya; Yu, Lei; Jiang, Yonglei; Lei, Yanbao; Korpelainen, Helena; Niinemets, Ülo; Li, Chunyang
Abstract: In this study, intra- and interspecific competition were investigated in early successional Salix rehderiana Schneider and later-appearing Populus purdomii Rehder under non-fertilized (control) and nitrogen (N)-fertilized conditions in the Hailuogou glacier retreat area. Our aim was to discover whether N is a key factor in plant–plant competition and whether N drives the primary succession process in a glacier retreat area. We analyzed differences in responses to intra- and interspecific competition and N fertilization between P . purdomii and S . rehderiana, including parameters such as biomass accumulation, nutrient absorption, non-structural carbohydrates, photosynthetic capacity, hydrolysable amino acids and leaf ultrastructure. In the control treatments, S . rehderiana individuals subjected to interspecific competition benefited from the presence of P . purdomii plants, as indicated by higher levels of biomass accumulation, photosynthetic capacity, N absorption, amino acid contents and photosynthetic N-use efficiency. However, in the N-fertilized treatments, P . purdomii individuals exposed to interspecific competition benefited from the presence of S . rehderiana plants, as shown by a higher growth rate, enhanced carbon gain capacity, greater amino acid contents, and elevated water-use efficiency, whereas the growth of S . rehderiana was significantly reduced. Our results demonstrate that N plays a pivotal role in determining the asymmetric competition pattern among Salicaceae species during primary succession. We argue that the interactive effects of plant–plant competition and N availability are key mechanisms that drive primary succession in the Gongga Mountain glacier retreat area.